Returning to homeland: Sigur Ros' Heima and the cultural landscapes of Post-Rock - Fletcher, Lawson (New Zealand Geographical Society, 2010)
The complex ways music sounds out space cannot be reduced to a mirror theory in which the contours of place are simply reflected in music's emotional architectures. Post-rock is a fruitful genre for problematising this notion, as its practitioners are motivated to sonorously re-construct, or at least mourn, the spatial erasures of late capitalism, epitomised by the apocalyptic melancholy of urban redevelopment represented in Canadian ensemble Godspeed You! Black Emperor. Icelandic quartet Sigur Rós maintain a skewed relationship to this primarily American genre, seeming instead to simply evoke the untouched natural beauty of their homeland, fulfilling discourses of Scandinavian 'purity' registered in the perennial critical descriptor for their sound: 'glacial'. Following the band's return to Iceland for a series of free concerts, the 2007 documentary Heima ostensibly affirms Western audiences' perception of their music as little more than the soundtrack to a 'Welcome to Iceland' tourism reel. Yet must things be read this way? This paper considers music's central role in constructing 'geographic knowledge' through a brief history of the affective cartography of post-rock, before critically reading the highly mediated forms - digital documentary, concert spectacle and recorded music - that constitute Sigur Rós' cultural landscape. I highlight the group's revival of the political project of post-rock through their accounting for capital's ecological refuse points, whilst paradoxically questioning their music as reflective of a 'natural' Iceland. Heima, that is, performs a conscious, if contradictory, audiovisual relationship to Iceland, one that is as much motivated by a conservative 'return home' as it is by a need to question one's homeland.